Group membership and radicalization: A cross-national investigation of collective self-esteem underlying extremism. (December 2020) - Ozer, Simon; Obaidi, Milan; Pfattheicher, Stefan
Uncertainty, perceived threats, and a generally insecure life attachment have been associated with endorsement of extremism. Furthermore, salient identification with a group can influence radicalized ways of addressing insecure life attachment through an established and sometimes extreme worldview and ideology. In the present study, we replicated the finding that an insecure life attachment is associated with a higher degree of extremism endorsement. Furthermore, we found similarities and differences in how this association was influenced by various aspects of group membership across dissimilar contexts and among majority and minority groups (e.g., Muslims and non-Muslims) from Denmark ( n = 223), India ( n = 147), and the United Kingdom ( n = 225). Consequently, our results indicate that general social psychological processes underlie radicalization and that different aspects of collective self-esteem can be central promoting or mitigating factors. Overall, our findings suggest an important interplay among life attachment, collective self-esteem, and extremism across Western and non-Western majority and minority groups.